Studi Teologis tentang Frasa “Injil Lain” dalam Galatia 1:6 dan Tantangan bagi Ortodoksi Masa Kini - Andrew Lucas Tjong; Boris Bambang Rahadi Setyawan (Jurnal Ilmiah Tafsir Alkitab, 2025)
Amidst the numerous proclamations claiming to be the gospel of Christ, messages that deviate from the core of the Gospel of Christ while cloaked in the name of Christ and the Gospel itself, a proper understanding of the term “different gospel” becomes essential for the preservation of Christian doctrinal orthodoxy. This article explores the theological meaning of the phrase "different gospel" in Galatians 1:6 and its implications for contemporary Christian’s orthodoxy. The research employs a hermeneutical approach (contextual, historical, lexical) and patristic study, particularly focusing on the writings of Tertullian, John Chrysostom, and Vincent of Lerins. The findings indicate that "another gospel" includes any message deviating from the Gospel of Christ—whether by obscuring Christ’s redemptive work, adding legalistic requirements for salvation, or ignoring the call to repentance. The integration of biblical interpretation and patristic witness emphasizes the importance of upholding apostolic doctrinal unity to preserve the purity of faith. This study contributes to the understanding and defense of Christian orthodoxy in response to doctrinal deviations.